KETERAMPILAN MENGOBSERVASI SISWA SEKOLAH DASAR DALAM PEMBELAJARAN IPS - Ode Sofyan Hardi; Kiki Rumantir (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2018)
The purpose of this study is to describe phenomena in thematic learning in elementary schools, where the ability to observe is included in the aspect of geographical skills. This research method uses descriptive method with a survey approach, by taking a sample of the school in SDN Rawamangun 12 Pagi, and taking a sample V class .The data analysis technique used is the description technique. Students who make observations can be seen from several activities below: Using various feelings to recognize an object; Record in detail the relevant facts of the object and everything around it; Identify similarities and differences; Using tools and materials to understand objects in detail. The results of this study basically students who study at SDN Rawamangun 12 Pagi have been able to observe social objects in social studies material using guided inquiry methods students experienced a significant increase. The use of models that prioritize aspects of high thinking in students, so that students experience good learning outcomes. Keywords: Skills, Observations, Social Sciences